A cross-sectional study to investigate short duration toxic consequences of smoking to lungs of asymptomatic smokers through spirometry and 6 min walk test - Bhupendra Kumar Jain; Ashwin Songra (Asian Journal of Medical Sciences, 2022)
Background: Cigarette smokers have a lower level of pulmonary function and physical fitness than non-smokers. Very little information is available for the short-term effects of smoking to lungs of asymptomatic smokers. Aims and Objectives: The main focus of this study is to evaluate short duration toxic consequences of smoking to the lungs of asymptomatic smokers through spirometry and 6 min walk test (6MWT). Materials and Methods: The present study is an observational cross-sectional study conducted in a tertiary care hospital which includes 160 individuals, 80 smokers and 80 non-smokers. The spirometric variables and 6MWT were performed to quantify smoking exposure. The whole statistics was analyzed using SPSS 21 and the mean between two groups was compared after applying standard Chi-square test. The means across more than 2 groups were compared after applying the standard analysis of variance (ANOVA) test. Results: Most of lung function parameter such as forced expiratory volume in 1 s (FEV1), FEV1%, FEV1/forced vital capacity % (FVC%), maximum mid-expiratory flow 25–75%, peak expiratory flow rate (PEFR), PEFR%, and maximum voluntary ventilation % is decreased significantly in asymptomatic smokers than non-smokers except FVC and FVC%. The 6MWT distance is also reduced gradually and significantly in asymptomatic smokers from 1–5 pack-years to 15–20 pack-years. Conclusion: Lung function parameters and 6MWT decreased significantly in asymptomatic smoker with increased quantum of pack-years. Therefore, early screening of high-risk smokers would lead to reduction of the clinical disease.